CsPbBr3 nanowire polarized light-emitting diodes through mechanical rubbing. Issue 40 (14th April 2020) - Wei, Yaping; Xu, Yinyan; Wang, Qian; Wang, Jianyue; Lu, Hongbo; Zhu, Jun
Abstract : CsPbBr3 nanowire polarized light-emitting diodes with low turn-on voltage were obtained through mechanical rubbing combined with an optimal device structure. Abstract : Anisotropic films composed of aligned CsPbBr3 nanowires (NWs) have been successfully fabricated using a mechanical rubbing method. The films with a dense and uniform morphology show polarization photoluminescence (PL) behavior. Combined with an optimal device structure, a polarized light-emitting diode (LED) with a turn-on voltage as low as 6.5 V was obtained.